2017
DOI: 10.1038/s41598-017-18271-4
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Nanocellulose Loaded with Bromelain: Assessment of Antimicrobial, Antioxidant and Physical-Chemical Properties

Abstract: Bacterial nanocellulose (BNC) has desirable properties for wound healing such as high purity, good shape retention, and high water binding capacity. Bromelain is a protease found in pineapple tissues and has been applied in several fields, it has anti-inflammatory and anticancer properties, promotes cell apoptosis, amongst others. In this work, a BNC based device for the controlled release of bromelain was developed. BNC were submersed in sterilized bromelain solution and incubated at 25 °C under 100 rpm for 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 79 publications
(62 citation statements)
references
References 47 publications
1
55
0
6
Order By: Relevance
“…MIC method [23,29] was adapted was adapted in 96-well microplates and performed in triplicate. The plate was stored in oven at 37 º C overnight.…”
Section: Minimum Inhibitory Concentration (Mic)mentioning
confidence: 99%
See 1 more Smart Citation
“…MIC method [23,29] was adapted was adapted in 96-well microplates and performed in triplicate. The plate was stored in oven at 37 º C overnight.…”
Section: Minimum Inhibitory Concentration (Mic)mentioning
confidence: 99%
“…Immobilization of biomolecules in CB has also been studied, either by increasing its antibacterial or enzymatic, and may providing a control release system [23][24][25]. Although previous studies show the antimicrobial action on nisin incorporated in CB and its antioxidant capacity [26], it is necessary to investigate the stability of this system.…”
Section: Introductionmentioning
confidence: 99%
“…Local application of bromelain has been shown to be rapid, effective, non-invasive, safe, easily performed at the bedside with minimal or no blood loss and negligibly interfere with natural wound healing processes (Koller, Bukovcan, Orsag, Kvalteni, & Graffinger, 2008;Muhammad & Ahmad, 2017). Bromelain also accelerates the healing of burn wounds in humans (Krieger et al, 2012), showing antioxidant and antimicrobial activities (Ataide, de Carvalho, et al, 2017;Ali, Milala, & Gulani, 2015;Dutta & Bhattacharyya, 2013;Praveen et al, 2014;Manosroi, Chankhampan, Pattamapun, Manosroi, & Manosroi, 2014).…”
Section: Bromelainmentioning
confidence: 99%
“…Commercial enzymatic debriding agents are available, and some previous studies reported their efficacy mainly in the treatment of burn wounds (Cordts et al, 2016;Rosenberg et al, 2014;Schulz et al, 2017) and to clear bruises and hematomas on boxers (Blonstein, Bromelain (Dutta & Bhattacharyya, 2013;Ali et al, 2015;Praveen et al, 2014;Manosroi et al, 2014;Ataide, de Carvalho, et al, 2017;Ekambaram et al, 2017) (Dutta & Bhattacharyya, 2013;Hu et al, 2011;Singer et al, 2010;Wu et al, 2012) (Blonstein, 1960;Cordts et al, 2016;Koller et al, 2008;Krieger et al, 2012;Rosenberg et al, 2004;Rosenberg et al, 2014;Schulz et al, 2017) Propolis ( Centella asiatica (Hong et al, 2005;Shukla, Rasik, Jain, et al, 1999;Gohil et al, 2010;Incandela et al, 2001;Zhang et al, 2016) (Shukla, Rasik, Jain, et al, 1999;Sawatdee et al, 2016;Gohil et al, 2010;Gul Satar et al, 2013;Sunilkumar et al, 1998;Rosen et al, 1967;Incandela et al, 2001;Poizot & Dumez, 1978;Suguna et al, 1996;Zhang et al, 2016) …”
Section: Bromelainmentioning
confidence: 99%
“…Other antimicrobial compounds are bromelain, a protease present in pineapple tissues, which also has anti-inflammatory and anticancer properties [243], lignin and lignin-derived compounds [244], and particularly curcumin, i.e. a naturally occurring polyphenolic compound isolated from Curcuma longa.…”
Section: Nanocellulose As a Carrier For Cell Delivery Into Skin Defectsmentioning
confidence: 99%